Conceptual Design Study of 13 MeV Proton Cyclotron - Silakhuddin Silakhuddin; S. Santosa (PPIKSN-BATAN, 2012)
A study to determine the conceptual design of a 13 MeV proton cyclotron for PET (Positron Emission Tomography) facility has been carried out. Based on studies on reactions of PET radioisotopes production, reaction cross-sections and some design references, a design of the proton cyclotron is proposed. The design criteria for the main components are decided using empirical and semitheoretical methods, as well as by referring to data regarding cyclotrons for PET production. The empirical method was carried out by using some data from operational experiences of BATAN cyclotron at Serpong, while the semitheoretical method was carried out by using the commonly used equations of cyclotron basic theory. The general layout of components and the main components, namely the ion source, the RF dees, the magnet, and the extractor are discussed. Based on the calculations and on the data used, the cyclotron is designed as a negative ion acceleration cyclotron with internal ion source. The designated proton energy and beam currents are 13 MeV and 50 µA. Its magnetic field is in the relativistic mode with sectors on the pole. The magnetic field intensity at the extraction radius is 12.745 kG and in the innermost radius is 12.571 kG. The magnetic poles consist of four sectors to make adequate space for components placement such as dees, ion source, extractor and beam probe. The dee angle is 430. The dee operates at 78 MHz on the fourth harmonic. A multifoil extractor is chosen to obtain an efficient operation.Received: 28 April 2011; Revised: 27 March 2012; Accepted: 30 April 2012